2022
DOI: 10.1177/20503121221126333
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled blood pressure and contributing factors among patients with hypertension at outpatient care of Bedele General Hospital, Southwest Ethiopia: A cross-sectional study

Abstract: Objective: This study aimed to assess uncontrolled blood pressure and contributing factors among patients with hypertension. Methods: Hospital-based cross-sectional study was conducted from January to April 2021 at Bedele General Hospital. Data were collected using the semi-structured questionnaire. All patients with hypertension were included using consecutive sampling technique unless ineligible. EpiData 4.4.2 was used for data entry, and SPSS 24.0 was employed for analysis. Binary logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…This study showed that the magnitude of uncontrolled BP was found to be 58.8% (95% CI: 54˗64%). This is in line with studies conducted in Tikur Anbesa General Specialized Hospital, Addis Ababa (59.9%) [ 34 ], Debre Tabor District Hospital, Northwest Ethiopia (57.1%) [ 20 ], Bale Zone Public Hospitals (56.7%) [ 35 ], Bedele General Hospital, Southwest Ethiopia (56.2%) [ 17 ], Public Health Facilities in Dessie City, Northeast Ethiopia (55.8%) [ 36 ], hospitals in Yaoundé, Cameroon (63.2%) [ 37 ], and a national survey in Vietnam (54.1%) [ 38 ]. However, it was higher than studies done at Nekemte Referral Hospital, Western Ethiopia (36.4%) [ 19 ], studies done at the University of Gondar Referral Hospital, Northwest Ethiopia (37% and 49.6%) [ 15 , 39 ], a primary care facility in South Africa (43%) [ 40 ] and studies conducted in Thailand [ 41 ], Chile [ 29 ], and Spain [ 42 ], which revealed uncontrolled BP of 24.6%, 36.9%, and 44.6%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…This study showed that the magnitude of uncontrolled BP was found to be 58.8% (95% CI: 54˗64%). This is in line with studies conducted in Tikur Anbesa General Specialized Hospital, Addis Ababa (59.9%) [ 34 ], Debre Tabor District Hospital, Northwest Ethiopia (57.1%) [ 20 ], Bale Zone Public Hospitals (56.7%) [ 35 ], Bedele General Hospital, Southwest Ethiopia (56.2%) [ 17 ], Public Health Facilities in Dessie City, Northeast Ethiopia (55.8%) [ 36 ], hospitals in Yaoundé, Cameroon (63.2%) [ 37 ], and a national survey in Vietnam (54.1%) [ 38 ]. However, it was higher than studies done at Nekemte Referral Hospital, Western Ethiopia (36.4%) [ 19 ], studies done at the University of Gondar Referral Hospital, Northwest Ethiopia (37% and 49.6%) [ 15 , 39 ], a primary care facility in South Africa (43%) [ 40 ] and studies conducted in Thailand [ 41 ], Chile [ 29 ], and Spain [ 42 ], which revealed uncontrolled BP of 24.6%, 36.9%, and 44.6%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Foti et al, (2021) proved that the effort to control blood pressure was more difficult in every five years of increasing age and mentioned diabetes and chronic kidney disease as the comorbid [25]. Sheleme et al, (2022) also stated that after 60 years old, the risk of uncontrolled blood pressure might increase by 4,4 times higher than the younger age. The elders who live with comorbidities potentially 2,2 times have uncontrolled blood pressure [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sheleme et al, (2022) also stated that after 60 years old, the risk of uncontrolled blood pressure might increase by 4,4 times higher than the younger age. The elders who live with comorbidities potentially 2,2 times have uncontrolled blood pressure [26]. These three researches proved that comorbidities as a significant factor of uncontrolled hypertension, whereas the research by Abegaz, Abdela, Bhagavathula, & Teni, (2018) noted differently that not comorbidities but sodium intake.…”
Section: Discussionmentioning
confidence: 99%
“…Pengetahuan yang kurang akan tekanan darah terkontrol untuk mencegah komplikasi, perburukan akibat komorbid dan penurunan kualitas hidup mendominasi dalam karakteristik kelompok intervensi. Sebuah laporan studi menunjukkan tekanan darah tidak terkontrol mayoritas pada pasien usia >60 tahun dengan resiko 4,4 kali dan pengaruh komorbid dapat meningkatkan resiko 2,2 kali [38]. Penelitian lainnya memberikan gambaran 50,2% tekanan darah sistolik tidak terkontrol akibat usia >60 tahun, ketidak patuhan pasien (53,4%) dan tenaga kesehatan dalam menerapkan pedoman terapi internasional (44,2%) [39].…”
Section: Kepatuhan Tekanan Darah Sistolik Dan Diastolikunclassified